Pharmacokinetic Profiling and Bioavailability Assessment of Meloxicam Solid dispersion Tablets - Namburu, Kumar; Murthy Kolapalli, Venkata Ramana; Yalavarthi, Prasanna; Chowdary Vadlamudi, Harini; Preethi Peesa, Jaya (Jordan Journal of Pharmaceutical Sciences, 2018)
The present investigation was focused on the comparative bioavailability assessment of meloxicam tablet prepared using modified gum karaya solid dispersion and commercial tablets of meloxicam. Non-blinded, open-label, crossover study was performed in six healthy volunteers for the determination of pharmacokinetic parameters. Blood samples were collected for 12 h at specified intervals of time after the administration of formulations and analyzed by suitable HPLC method. The pharmacokinetic parameters such as maximum plasma concentration (Cmax), time to reach Cmax (tmax), elimination rate constant (Kel), biological half-life (t½), absorption rate constant (Ka) and area under curve (AUC0-12 and AUC0-) were determined. Significant difference in the bioavailability of commercial meloxicam tablets and modified gum karaya solid dispersion tablets of meloxicam has been reported from the studies. The results clearly indicated an enhancement in the bioavailability of meloxicam prepared tablets compared to commercial meloxicam tablets.